Adverse reaction report and retrospective analysis of black hairy tongue caused by linezolid. (2020) - Luo, Shaohua; Luo, Qian; Gao, Xinglin; Li, Jing
Abstract: The adverse reaction of Black Hairy Tongue (BHT) caused by linezolid is rare. We reports a case of linezolid-induced BHT, and reviews relevant literatures at home and abroad. It aims to provide a safe and reasonable basis for clinical medication use. A 14-year-old adolescent with pneumonia caused by methicillin-resistant Staphylococcus aureus (MRSA) developed a rash and pruritus due to Vancomycin. Instead, the patient was given linezolid 600mg q12h in injection during hospitalization and in tablet after discharge. On the 14th day after injection and the second day after oral administration the patient showed BHT without other abnormal taste symptoms. But all the symptoms could be tolerated and he completed the therapy course of linezolid. Tongue symptoms completely disappeared on the 8th day after drug withdrawal. Based on the Karch and Lasagna evaluation methods and the cause-and-effect evaluation methods of the WHO collaborating center for international adverse drug reaction (ADR) monitoring, it is likely that this patient had a BHT caused by linezolid. The mean time of occurrence of BHT was 14.36 days, and the mean time of symptom disappearance was 23.43 days after drug administration. When linezolid is prescribed to patients, especially those with atopy, the patient's tongue should be closely observed and good oral hygiene is recommended.